O papel das relações sociais e da atenção social durante tarefas cooperativas em Callithrix jacchus - Cerqueira, Rafaela Cobuci (2012)
Several studies on nonhuman primates show that the relationships between individuals strongly influence the expression of cooperative behavior, both in natural environment and in captivity settings. Recent studies suggest that cooperative breeders present outstanding performance in tasks involving social cognition, such as cooperative tasks with experimental apparatuses. In experimental research on this subject it is crucial to differentiate between real cooperation (or communicative cooperation, mediated by social attention) and by-product cooperation that results from simultaneous actions of individuals. The present study assessed, in Callithrix jacchus, a cooperative breeder species, if social relationships and social attention between subjects are important factors during performance in cooperative tasks. During the experimental procedure the animals participated in three different cooperative tasks: cooperation task, prosocial task and control task. Diverging from the literature, matrix correlation tests revealed no significant relationship between grooming or proximity and the execution of the tasks, suggesting that other factors such as age or hierarchy may have an effect on the performance in cooperative tasks in this species. There was also no relationship between the execution of the cooperative tasks and social glances, suggesting that there was no social attention during the tasks. Moreover, there were lower rates of social glances in the cooperative tasks as opposed to the control tasks. However, the small number of pulls in prosocial tasks suggests that the animals distinguished between tasks that benefited only a partner and tasks that generated benefits to themselves, choosing the latter. We conclude that, for the tasks presented in this study, we could neither detect the role of social relationships on the cooperative tasks nor assert that there were true cooperation and prosocial behavior